Study of Excess Sludge Reduction in Conventional Activated Sludge Process by Heating Returned Sludge - Mahmoudi, Parviz; Takdastan, Afshin; Alavi, Nadali; A.J. Mosavi, Ali; Kaydi, Neda (Asian Journal of Chemistry, 2012)
The use of conventional activated sludge as a biological wastewater treatment process has been employed to treat a wide variety of wastewater. The ultimate disposal of excess sludge generated from activated sludge processes has been one of the most challenging problems for waste water treatment utilities in order to solve the problem of excess sludge production. This paper investigated the effect of temperature on excess sludge reduction in activated sludge process, therefore, returned sludge temperature was increased from 30 to 70 ºC, stepwise every 10 ºC at the time concentrating on each step for 1 h. After reaching steady state in the system, we made use of sampling and testing parameters such as COD, MLSS, MLVSS, SVI, BOD5 and yield coefficient. Results showed that increasing the temperature from 30 to 40 ºC increased the yield coefficient from 0.68 to 0.73. Further increase of the temperature up to 60 ºC reduced the yield coefficient to 0.33 and increased residual COD in the effluent from 89 to 195 mg/L, which is less than agricultural reuse standard. Also in this temperature, sludge reduction rate was about 46.8 % and SVI rate was about 44 mg/L. At 70 ºC increase in effluent COD and turbidity was noticed. It also did not meet the wastewater disposal standard and the wastewater gave out bad odor and had bad yield coefficient.